Determinants of nutritional status and osteosarcopenia based on comprehensive geriatric assessment in elderly outpatients with multimorbidity, with a particular focus on chronic heart failure - Fatyga-Kotula, Paulina (2022)
The aim of this cross-sectional research was to identify the determinants of nutritional status and osteosarcopenia in elderly outpatients with multimorbidity (particularly chronic heart failure), using comprehensive geriatric assessment. This was a cross-sectional study including patients from the Geriatric Clinic of the University Hospital in Cracow, Poland. The study was approved by the Bioethics Committee. Patients aged 60 years or older who provided written informed consent were enrolled to the study from October 2010 to February 2014. Regression analysis identified the following determinants of malnutrition: the number of comorbidities, female sex, cognitive impairment (based on the MMSE), the presence of valvular heart disease, and increased levels of IL-8, sTNFRII, and osteoprotegerin. Increased IL-18 levels were associated with a lower risk of malnutrition. GDS score and NT-proBNP levels remained significant predictors of low handgrip strength. Older age and a higher percentage of lower-extremity fat mass were independent predictors of lower gait speed. Better nutritional status was associated with higher gait speed. Older age, poorer nutritional status, and a higher number of comorbidities were associated with a longer time to complete the TUG test. Age and percent of lower-extremity fat mass negatively affected 6MWT outcomes.
Keywords: comprehensive geriatric assessment; malnutrition; multimorbidity; sarcopenia